Differential Attention Functioning in Pediatric Chronic Kidney Disease - Duquette, Peter J.; Gipson, Debbie S.; Hooper, Stephen R. (Frontiers in Human Neuroscience, 2022)
Abstract Objective: To compare specific attention functions for school-age children with chronic kidney disease (CKD) to those of a typically developing control group. Methods: A cross-sectional study examined attention dimensions for children and adolescents with CKD (n = 30) and compared them to a typically developing control group (n = 41). The CKD group consisted of those receiving maintenance dialysis (n = 15) and those with mild/moderate CKD treated conservatively (n = 15). Measures aligning with Mirsky’s conceptual multidimensional model of attention were selected to compare groups across five dimensions of attention: Focus/Execute, Sustain, Stability, Shift, and Encode. Results: Significant group differences were revealed, with the CKD group performing worse than controls on the Focus/Execute, Sustain, and Encode dimensions. The CKD group also had a larger proportion of children with scores one standard deviation or more below the mean on the Shift and Encode domains, suggesting an at-risk level of functioning in these dimensions. Secondary analyses showed disease severity to be correlated with worse attention functions for children with CKD. Conclusions: Children with CKD may be vulnerable to subtle, specific deficits in numerous attention dimensions relative to their typically developing peers, particularly for those with more severe disease.